2013
DOI: 10.1007/s10803-013-2016-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Infection During Pregnancy and Autism Spectrum Disorders

Abstract: We conducted a nested case-control study including 407 cases and 2075 frequency matched controls to investigate the association between maternal infections during pregnancy and risk of autism spectrum disorders (ASD). Cases, controls, and maternal infections were ascertained from Kaiser Permanente Northern California clinical databases. No overall association between diagnoses of any maternal infection during pregnancy and ASD (adjusted odds ratio [ORadj] = 1.15, 95% confidence interval [CI] 0.92 – 1.43). Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
165
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(188 citation statements)
references
References 47 publications
10
165
1
4
Order By: Relevance
“…Some studies suggest fever as a correlate (Atladottir et al, 2012), with this risk potentially tempered by anti-fever medications, such as Advil, Tylenol, or Nyquil (Zerbo et al, 2013). A more expansive study by Zerbo et al (2015) found that maternal infection diagnosed at a hospital admission, especially bacterial ones, correlated with increased risk of ASD. A yet-larger 2015 study of over 24 000 Swedish ASD cases observed increased ASD rates among offspring of mothers hospitalized the year before pregnancy; risk for ASD increased under any inpatient diagnosis, including both viral and bacterial (Lee et al, 2015).…”
Section: Congenital Infectionmentioning
confidence: 99%
“…Some studies suggest fever as a correlate (Atladottir et al, 2012), with this risk potentially tempered by anti-fever medications, such as Advil, Tylenol, or Nyquil (Zerbo et al, 2013). A more expansive study by Zerbo et al (2015) found that maternal infection diagnosed at a hospital admission, especially bacterial ones, correlated with increased risk of ASD. A yet-larger 2015 study of over 24 000 Swedish ASD cases observed increased ASD rates among offspring of mothers hospitalized the year before pregnancy; risk for ASD increased under any inpatient diagnosis, including both viral and bacterial (Lee et al, 2015).…”
Section: Congenital Infectionmentioning
confidence: 99%
“…But they found women with bacterial infections, were at increased risk of delivering a child with ASD. 23 Atladóttir et al conducted a study on children in Denmark from 1980, through 2005. 50 They found no association between maternal infection and ASDs, but viral infection and bacterial infection were found to be connected to ASD in the offspring in the first trimester and in the second trimester respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, autistic disorder cannot be traced to a Mendelian (single-gene) mutation or to single chromosome abnormalities such as fragile X syndrome or 22q13 deletion syndrome 14 . There may be significant interactions among mutations in several genes, or between the mutated genes and environment 15,16 . All known teratogens related to the risk of autism appear to act during the first eight weeks from conception 16 .…”
Section: Fig1: Clinical Features Of Autismmentioning
confidence: 99%
“…There may be significant interactions among mutations in several genes, or between the mutated genes and environment 15,16 . All known teratogens related to the risk of autism appear to act during the first eight weeks from conception 16 . Environmental factors that contribute to or exacerbate autism, and important in upcoming research, include heavy metals, certain foods, solvents, infectious disease, phthalates, phenols and diesel exhaust used in pesticides alcohol, brominated flame retardants illicit drugs plastic products, vaccines smoking 17 .…”
Section: Fig1: Clinical Features Of Autismmentioning
confidence: 99%